Porosity, water sorption and solubility of denture base acrylic resins polymerized conventionally or in microwave (Journal of Applied Oral Science, 2022)
The proper selection of polymerization cycle is important to prevent overheating of the monomer that could cause degradation, porosity and, consequently, deleterious effects on the denture base properties. Objective: This study evaluated the porosity, water sorption and solubility of acrylic resins (Vipi Cril-VC and Vipi Wave-VW) after conventional or microwave polymerization cycles. Material and Methods: Specimens (n = 10) were made and cured: 1-WB = 65°C during 90 min + boiling during 90 min (VC cycle - control group); 2-M25 = 10 min at 270 W + 5 min at 0 W + 10 min at 360 W (VW cycle); 3-M3 = 3 min at 550 W; and 4-M5 = 5 min at 650 W. Afterward, they were polished and dried in a dessicator until a constant mass was reached. Specimens were then immersed in distilled water at 37°C and weighed regularly until a constant mass was achieved. For porosity, an additional weight was made with the specimen immediately immersed in distilled water. For water sorption and solubility, the specimens were dried again until equilibrium was reached. Data were submitted to 2 way-ANOVA and Tukey HSD (α=0.05). Results: Porosity mean values below 1.52% with no significant difference among groups for both materials were observed. Resins showed water sorption and solubility values without a significant difference. However, there was a significant difference among groups for these both properties (P<0.013). The highest sorption (2.43%) and solubility (0.13%) values were obtained for WB and M3, respectively. Conclusions: The conventional acrylic resin could be polymerized in a microwave since both the materials showed similar performance in the evaluated properties. Shor